Divergent Synthesis of γ‐Amino Acid and γ‐Lactam Derivatives from meso‐Glutaric Anhydrides. Issue 59 (30th September 2020) - Smith, Simon N.; Craig, Ryan; Connon, Stephen J.
Abstract: The first divergent synthesis of both γ‐amino acid and γ‐lactam derivatives from meso ‐glutaric anhydrides is described. The organocatalytic desymmetrisation with TMSN3 relies on controlled generation of a nucleophilic ammonium azide species mediated by a polystyrene‐bound base to promote efficient silylazidation. After Curtius rearrangement of the acyl azide intermediate to access the corresponding isocyanate, hydrolysis/alcoholysis provided uniformly high yields of γ‐amino acids and their N ‐protected counterparts. The same intermediates were shown to undergo an unprecedented decarboxylation–cyclisation cascade in situ to provide synthetically useful yields of γ‐lactam derivatives without using any further activating agents. Mechanistic insights invoke the intermediacy of an unconventional γ‐ N ‐carboxyanhydride (γ‐NCA) in the latter process. Among the examples prepared using this transformation are 8 APIs/molecules of considerable medicinal interest. Abstract : Desymmetrisation : A divergent synthetic strategy to access both γ‐amino acid and γ‐lactam derivatives by treatment of meso ‐glutaric anhydrides with TMSN3 is reported (see scheme).